Zero Trust Threat Modeling: STRIDE-ZTA - Nymalm, Amy (My University, 2025)
The concept of perimeterless security has gained popularity, today known as zero trust. Zero trust architecture is complicated, consisting of complex logical components that change the security posture of a system. This change is driven by the need for better security, but with such a change in architecture, it is possible that new threats arise, or old threats are not mitigated after all. To determine the threats present in a system, threat modelling can be used. However, with the changes zero trust architecture brings, traditional threat modelling methods might not be sufficient in locating all possible threats. This thesis aims to find answers to the questions of what threat modeling framework is sufficient for performing threat modeling on zero trust systems and how zero trust affects the threat modeling process. In addition, this thesis will focus on an interface in the 5G radio access network, the Xn-interface, and examine if zero trust affects the threat modeling process on the interface. Relevant research is found though a literature review. Based on the research done in this thesis, zero trust does not severely change the way threat modeling is performed, but benefits from certain additions compared to more traditional threat models. These additions include possible new threats to consider, as well as a shift in perspective so that insider threats and compromised assets are better accounted for during the threat modeling process. A threat modeling methodology that takes these concerns into consideration is proposed: STRIDE-ZTA. STRIDE-ZTA is a threat model designed for zero trust systems that also takes zero trust maturity into account. A proof of concept is performed on the proposed model using the Xn-interface to examine the usability of the model, as well as to examine the effects of zero trust on threat modeling the Xn-interface. Based on the proof of concept, STRIDE-ZTA is usable, and zero trust affects the threat modeling of the Xn-interface in the same way as threat modeling in general. Future research of STRIDE-ZTA and zero trust maturity can further polish the model to maximize its usability.
Keywords: Zero trust maturity, threat modeling, 5G, Xn-interface